Anatomic structures at risk in anteroposterior screw fixation of posterior malleolar fractures: A cadaver study. Issue 2 (February 2021) - Peng, Jianguang; McKissack, Haley; Yu, Jonathan; He, Jun Kit; Montgomery, Tyler; Moraes, Leonardo; Alexander, Bradley; Shah, Ashish
Highlights: Anterior anatomic structures can be injured during anterior-posterior (AP) screw placement during posterior malleolus fracture fixation. During fixation the middle screw was 1.2 (CI 0.24–2.1) mm from the anterior tibial artery and 4.9 (CI 3.6–6.2) mm from the DPN. It put both the anterior tibial artery and the DPN at risk and was significantly closer to these structures than both the medial and lateral screws ( p  < 0.001). Although the perpendicular trajectory of a lateral screw may create a more stable construct, our results suggest that a medially placed screw reduces risk of damage to nearby structures relative to screws introduced more centrally or laterally. Abstract: Introduction: Percutaneous anterior-posterior (AP) screw is an option for posterior malleolus fracture fixation when the fracture fragment can be reduced indirectly by the mean of ligamentotaxis. However, anterior anatomic structures could be injured during screw placement. Materials and methods: Eleven below-knee cadavers were employed for the placement of AP screws in an attempt of fixing assumed Haraguchi Type-I posterior malleolar fractures. Three entry points were selected as medial to the anterior tibial tendon (ATT), lateral to the ATT, and lateral to the extensor digitorum longus (EDL). Three AP screws were placed under guidance of fluoroscopy. After dissection, measurements were made (mm) from each screw to nearby structures. Distances were calculated and damage to structures was documented. Results: Mean, minimum, and maximum distances from the medial screw to the greater saphenous vein, TA, EHL, anterior tibial artery (ATA), and deep peroneal nerve (DPN), were 18.1 (12–25) mm, 2.0 (0–5) mm, 13.6 (9–20) mm, 16.6 (9–25) mm, and 20.1 (12–27) mm. From the middle screw to the ATA, DPN, TA, EHL, and EDL, were 1.2 (0–3) mm, 4.9 (3–9) mm, 3.8 (1–7) mm, 0.4 (0–2) mm, and 13.6 (10–18) mm. From the lateral screw to the superficial peroneal nerve (SPN), EDL, DPN, and ATA, were 10.8 (0–16) mm, 1.2 (0–4) mm, 15.9 (11–25) mm, 19 (15–27) mm. The SPN was found partially cut by the lateral screw on 1 specimen. Conclusions: Lateral and middle percutaneous AP screw placement put certain anatomic structures at-risk of injury. Medial screw placement did not result in appreciable damage to adjacent structures. Entry point of AP screws should be selected with respect to posterior malleolar fracture and anatomic structures. Level of evidence: IV.